Gummosin, a sesquiterpene coumarin from Ferula assa-foetida is preferentially cytotoxic to human breast and prostate cancer cell lines - Milad Iranshahi; Faegheh Farhadi; Babak Paknejad; Parvin Zareian; Mehrdad Iranshahi; Masoumeh Karami; Seyed Reza Abtahi (Mashhad University of Medical Sciences, 2019)
Objective: The present study was conducted to find cytotoxic compounds from oleo-gum-resin of Ferula assa-foetida (asafoetida). Materials and Methods: A dichloromethane extract of asafoetida was subjected to different chromatography analyses (including column chromatography, preparative thin layer chromatography and high performance liquid chromatography) to isolate its bioactive sesquiterpene coumarins. The structures of isolated compounds were elucidated through 1H-NMR spectra interpretation and comparison with those reported in the literature. To measure the cytotoxic activity of pure compounds, a non-fluorescent substrate called resazurin (alamarBlue®)was used in this study. Human breast and prostate cancer cell lines (MCF-7 and PC-3, respectively) and a normal human embryonic stem cell (NIH) were treated with different concentrations (50, 25, 12.5 and 6.25 µg/mL) of pure compounds. Results: In this study, 10 sesquiterpene coumarins were isolated from oleo-gum-resin of F. assa-foetida and cytotoxic activity of 6 compounds was tested against MCF-7 and PC-3 cell lines and NIH cells. Badrakemin acetate (7), ferukrinone (8) and deacetyl kellerin (10) were found for the first time in the oleo-gum-resin of F. assa-foetida. Gummosin (4) showed moderate cytotoxic activity with IC50 values of 30 and 32.1 µg/mL against PC-3 and MCF-7 cell lines, respectively. None of the isolated compounds showed toxicity against NIH as a normal human cell line. Conclusion: The preferential cytotoxic activity of gummosin against cancer cell lines is reported for the first time in this study.